A General Scheme for a Heterogeneous Manifold of Transitions Un schéma général pour un ensemble hétérogène de transitions - Hochmuth, Reinhard (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract A general praxeological scheme is applied to express relations between praxeological blocks depending on the goal of the analysis and the specific institutional setting within which a mathematical praxeology is considered. Besides its heuristic function, the scheme provides a framework for context dependent categorizations of praxeologies. The poster exemplarily illustrates the application of the scheme to two different contexts: measures supporting students in their first year of study; the use of mathematics in engineering sciences. Keywords: ATD; categorization of praxeologies; mathematic students; mathematics in engineering Résumé Un schéma praxéologique général est utilisé pour décrire les relations entre des blocs praxéologiques en fonction de l’objectif de l’analyse et de l’environnement institutionnel dans lequel on considère les praxéologies mathématiques. À côté de cette fonction heuristique, le schéma propose un cadre pour la catégorisation des praxéologies à partir de deux contextes différents : des mesures de support pour les étudiants universitaires de première année, l’utilisation des mathématiques dans les sciences de l’ingénieur. Mots-clés : TAD, Catégorisation des praxéologies; Étudiants en mathématiques; Mathématiques en ingénierie